Screening for undiagnosed bleeding disorders in post-tonsillectomy bleed patients: Retrospective review and systematic review of the literature. (September 2019) - Gitomer, Sarah A.; Shebha Anand, Grace; Bradley, Hallie E.; Kumar, Manish; Ouellette, Lara; Musso, Mary F.
Abstract: Objectives: There is currently no standard for screening children with post-tonsillectomy bleeds (PTB) for coagulopathy disorders. This study aims to identify children with occult coagulopathy diagnosed at PTB and to identify factors associated with diagnosis. A systematic review of the literature further identified trends in this topic. Methods: A retrospective chart review of patients returning to the operating room for PTB at a tertiary children's hospital was undertaken from 2012 to 2016. A systematic review using Medline OVID was subsequently performed. Results: Of 12, 503 tonsillectomies, 311 children (52% male, mean age 8 years) required surgery for PTB (2.5% rate). Twenty-one patients (7%) had multiple episodes. Only two patients (0.6%) (both with known coagulopathy) underwent pre-tonsillectomy labs and 260 (84%) had labs at PTB. Six patients (2%) were diagnosed with a new coagulopathy, most commonly von Willebrand's Disease (vWD) in five (2%). Three patients (1%) were diagnosed at first PTB and three (1%) at second PTB. Of the three diagnosed at second PTB, two had normal partial thromboplastin time (PTT). In systematic review, 1243 manuscripts were reviewed and 8 papers discussing this topic are presented. Conclusion: Occult coagulopathy was rarely diagnosed at PTB, but this may be limited by inconsistent screening. PT and PTT are not sensitive tests for vWD, and normal coagulation labs may lead to delayed diagnosis. The literature reveals occult coagulopathy is rare but often diagnosed after severe or recurrent hemorrhage. In order to provide efficient care and medical management, a standardized algorithm and sensitive labs for screening PTB patients are needed.